Copper‐Catalyzed Perfluoroalkylthiolation of Alkynes with Perfluoroalkanesulfenamides. Issue 29 (23rd June 2016) - Tlili, Anis; Alazet, Sébastien; Glenadel, Quentin; Billard , Thierry
Abstract: Copper‐catalyzed direct perfluoroalkylthiolation of alkynes by using the corresponding perfluoroalkanesulfenamide reagent is reported. The selective mono‐ and bis‐perfluoroalkylthiolation of alkynes can be conducted under very mild conditions (no base, room temperature) in very good to excellent yields. This approach, which uses a low toxicity, inexpensive copper catalyst that incorporates a commercially available ligand, is applied in the absence of any additional base. Preliminary mechanistic investigations shed some light on the nature of the unprecedented reactivity observed. Abstract : One or two? Selective mono‐ and bis‐perfluoroalkylthiolation of alkynes could be performed with perfluoroalkanesulfenamides under copper‐catalyzed base‐free conditions (see scheme). This original approach seems to occur through an unprecedented pathway.